Agricultural transformation and market integration in the ASEAN region: Responding to food security and inclusiveness concerns summary report on the national inception workshop in Cambodia - Southeast Asian Regional Center for Graduate Study and Research in Agriculture (Southeast Asian Regional Center for Graduate Study and Research in Agriculture, 2017)
The National Inception Workshop is one of the required and critical activities involved in the project titled, “Agricultural Transformation and Market Integration in the ASEAN Region: Responding to Food Security and Inclusiveness Concerns” (ATMI-ASEAN). The project is a response to the challenges confronting Southeast Asia’s food security and inclusive agricultural growth agenda due to structural transformation in the region. The integration of agricultural markets within ASEAN is also high in its policy agenda given the current pressure of the ASEAN Economic Community. Although some developmental steps have been made, such as the emergency rice reserve, and establishment of APTERR, the overall progress in the implementation of the ASEAN food security framework has remained limited. Based on a broader understanding of the regional agricultural transformation process, the proposed project will assist in (1) the preparation of national and regional roadmaps for the development of key regional food and agri-based value chains; (2) development of mechanisms for improved coordination between national and ASEAN food reserves and food security policies; (3) inform the process of harmonization of food safety and quality standards among AMS; and (4) improvement in R&D cooperation to improve practices in key agri-based and food value chains.